The Role of Digital Storytelling in Developing Students’ Higher-Order Thinking Skills (HOTS) - Nur Fauziah; Abdur Rosyid; Diana Budi Darma; Fithriyah Inda Nur Abida (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the implementation process of Digital Storytelling (DST) and examine its effects on the higher-order thinking skills (HOTS) of secondary school students in Surabaya. Using a quasi-experimental design, the research integrates quantitative data (HOTS tests, N-gain) and qualitative data (observations, interviews, and DST product analysis). The findings indicate a significant improvement in students’ HOTS scores, increasing from an average of 61.25 (medium–low) to 78.75 (medium–high), with an N-gain of 0.46 (medium–high). The rubric-based analysis of DST products revealed students’ abilities to generate original ideas, integrate multimedia, construct logical narratives, analyze information, and reflect on their thinking processes. The most substantial improvement occurred in the creating dimension, followed by analyzing and evaluating—aligned with the nature of DST as a creative production activity. This study highlights that DST functions not only as an instructional medium but also as a pedagogical instrument that fosters HOTS development through project-based learning, collaboration, and multimedia integration. The findings provide empirical insights for enhancing 21st-century learning strategies in Indonesia and offer an adaptable DST implementation model for teachers to support students’ creativity, analytical skills, and critical reflection.